The Influence of Online Games on The Social Behavior of High School Students - Aisyah Farah Muminah; Budi Haryanto; Anita Puji Astutik (Edumaspul: Jurnal Pendidikan, 2023)
Several aspects of life are currently undergoing transformations due to the rapid advancement of communication technology, and one such aspect is entertainment, specifically online games. The primary purpose of online games is to provide amusement to individuals and prevent them from experiencing boredom after completing routine tasks. However, individuals become addicted to online games primarily due to the intense gameplay, particularly among teenage groups. Even excessive online games has negative consequences, including social inequality such as timelessness and a decline in manners. This study aimed to examine the correlation between online games and the social behavior of high school students in the Bangil District. This study employed a quantitative method utilizing an analytical survey. The sampling technique employed was purposive sampling, conducted in several coffee shops within the Bangil District, with a sample size of 50 respondents. The findings of this study revealed a negative impact of online games on the social behavior of high school students, as indicated by the equation Y = 5.066 + 0.848X, demonstrating a significant influence. The correlation between X and Y is 0.774, indicating a negative relationship between the variables. The remaining 0.226 falls outside the scope of this investigation. There existed a strong and significant negative relationship between online games and the social behavior of high school students. The impact of online games on students' social behavior manifested in several negative aspects, including the usage of harsh language, disruption of daily productivity leading to health deterioration, failure to keep promises to others, neglecting religious worship, abandoning tasks, and a decrease in the display of empathy towards others. Keywords: Online Games, Social Behavior, Student